Creativity interwoven into the fabric of learning, an example from a postgraduate nutritional science module - Nerantzi, Chrissi; Moravej, Haleh; Iosifidou, Ioanna; Nani Silva, Leticia (PRISM: Casting New Light on Learning, Theory and Practice, 2020)
This paper is a patchwork of reflective accounts linked to the experience of a postgraduate module that was co-designed by a teaching team using creative approaches to learning. The teaching team provide a rationale for the design and approaches used in this module. The reflective accounts of these two students that have been included, should be seen as two cases that provide insights into these students’ experience on the module and aided to conduct a preliminary evaluation linked to these and not the whole cohort.